Characteristics of women admitted to medium secure care: a comparison of patients admitted to specialised single-sex and mixed-sex services in an English forensic psychiatric hospital - McCarthy, Lucy; Westhead, Jodie; Gibbon, Simon; Hatcher, Ruth M.; Clarke, Martin (Frontiers in Psychiatry, 2025)
BackgroundForensic mental health care has evolved from mixed-sex provision to specialised sex-specific services. It is important to understand how the characteristics of women admitted to medium secure care have changed over time and how this may impact on their outcomes after discharge.ObjectiveThe study aims to describe and compare admission and discharge characteristics of two consecutive cohorts; women admitted between 1983 and 2001 to a mixed-sex medium secure care (‘Mixed’ cohort) and women admitted between 2005 and 2013 to single-sex medium secure care (‘Specialised’ cohort).MethodsData came from a 30-year study of outcomes for first admissions to an NHS medium secure hospital (the ALACRITy study). Follow-up data were available up to a census date of June 30th 2013.Results93 women comprised the Mixed cohort (mean age 29.3 years; 81% White ethnicity; 49% personality disorder diagnosis) and 45 women comprised the Specialised cohort (mean age 32.4 years; 76% White ethnicity; 49% personality disorder diagnosis). The Specialised cohort were more likely than the Mixed cohort to be admitted from high security, or under a forensic section of the Mental Health Act. The Specialised cohort were more likely than the Mixed cohort to have previous convictions, or to have committed a ‘grave’ index offence warranting a life sentence. Over 95% of all women had received previous inpatient psychiatric care. The Specialised cohort had greater prevalence of alcohol use, self-harm and childhood adversity than the Mixed cohort. At the census, 99% of the Mixed cohort and 42% of the Specialised cohort had been discharged. Women in the Specialised cohort had a longer median length of stay than the Mixed cohort; 859 days and 229 days respectively. Over 80% of patients in the Mixed cohort were readmitted during the follow-up period.ConclusionThe study provides empirical data for two consecutive cohorts of women admitted to one medium secure hospital over the course of thirty years. Women admitted to single-sex services had more criminological and adverse trauma histories than women admitted to the earlier mixed-sex service. Further research is required to establish the long-term outcomes of women admitted to specialised single-sex medium secure care.